Inward Rectifier Potassium Channels (Kir2.x) and Caveolin-3 Domain-Specific Interaction: Implications for Purkinje cell-Dependent Ventricular Arrhythmias - Vaidyanathan, Ravi (Circ Arrhythm Electrophysiol, 2018)
BACKGROUND: In human cardiac ventricle, I(K1) is mainly comprised of Kir2.1, but Kir2.2 and Kir2.3 heterotetramers occur and modulate I(K1.) LQT9-associated CAV3 mutations cause decreased Kir2.1 current density, but Kir2.x heterotetramers have not been studied. Here we determine the effect of LQT9-CAV3 mutation F97C on Kir2.x homo- and heterotetramers and model associated arrhythmia mechanisms. METHODS AND RESULTS: Super-resolution microscopy, Co-immunoprecipitation, cellular electrophysiology, on-cell Western blotting, simulation of Purkinje and ventricular myocyte mathematical models were used. Kir2.x isoforms have unique sub-cellular co-localization in human cardiomyocytes and co-immunoprecipitate with Cav3. F97C-Cav3 decreased peak inward Kir2.2 current density by 50% (−120mV p-value=0.019) and peak outward by 75% (−40mV p-value<0.05) but did not affect Kir2.3 current density. FRET efficiency for Kir2.2 with Cav3 is high and on-cell Western demonstrates decreased Kir2.2 membrane expression with F97C-Cav3. Cav3-F97C reduced peak inward and outward current density of Kir2.2/Kir2.1 or Kir2.2/Kir2.3 heterotetramers (p<0.05). Only Cav3 scaffolding and membrane domains co-IP with Kir2.1 and Kir2.2 and Kir2.x-N-terminal Cav3 binding motifs are required for interaction. Mathematical Purkinje, but not ventricular, myocyte model incorporating simulated current reductions, predict spontaneous delayed-after-depolarization (DAD) mediated triggered activity. CONCLUSIONS: Kir2.x isoforms have a unique intracellular pattern of distribution in association with specific Cav3 domains, and that critically depends on interaction with N-terminal Kir2.x Cav3 binding motifs. LQT9-CAV3 mutation differentially regulates current density and cell surface expression of Kir2.x homomeric and heteromeric channels. Mathematical Purkinje cell model incorporating experimental findings suggests DAD-type triggered activity as a possible arrhythmia mechanism.